Ketulusan dan Kejujuran Pebisnis Menurut (Amsal 11:1-3) - Julius M. Hutabarat; Nobel A. Tampubolon; Lisda Waty Harianja; Grecetinovitria Merliana Butar-butar (Lembaga Pengembangan Kinerja Dosen, 2024)
Business is an activity carried out individually or in groups by producing and selling goods and services to gain financial profit as long as the interests and rights of other people are not sacrificed. In the book of proverbs, a businessman must have an attitude of honesty because Allah hates people who are dishonest and loves people who seek justice and sincerity is a factor that encourages people to behave honestly. When someone leads sincerely, they help other people to live and behave honestly